Quality Analysis of Public Services for AK-1 Application at Disnakertrans Banten Province with Fuzzy Servqual - Finira, Dwinita Chika; Kusumah, Lien Herliani (Journal of International Conference Proceedings, 2023)
The Manpower and Transmigration Office, also known as Disnakertrans provides direct services to the community, including the issuance of the AK-I cover letter commonly known as the "Kartu Kuningâ€. A significant issue has emerged at the Disnakertrans, where the process of obtaining an AK-1 takes more than 20 minutes, surpassing the average time expected by job seekers. Additionally, daily quotas for AK-I issuance are restricted due to Covid-19 regulations. To assess and enhance service quality for AK-I issuance at Disnakertrans Banten Province, a service satisfaction method is imperative. This study employs the Fuzzy Servqual method. The research reveals a noteworthy negative gap in the reliability dimension, particularly concerning two attributes. The first attribute (Question 7) addresses the ability of officers to guide job seekers through the AK-1 application process. The second attribute (Question 8) pertains to the accuracy of officers in entering data according to the specified requirements. These findings underscore the importance of addressing issues related to the reliability dimension, particularly the officer's ability to guide the application process and ensure accurate data entry. By focusing on these aspects, Disnakertrans can make targeted improvements to enhance overall service quality and meet the expectations of service users.